2007
DOI: 10.2220/biomedres.28.85
|View full text |Cite
|
Sign up to set email alerts
|

Oral treatment with L-lysine and L-arginine reduces anxiety and basal cortisol levels in healthy humans

Abstract: Dietary supplementation with an essential amino acid L-lysine has been shown to reduce chronic anxiety in humans with low dietary intake of L-lysine. A combination of L-lysine and L-arginine has been documented to normalize hormonal stress responses in humans with high trait anxiety. The present study was carried out in one hundred eight healthy Japanese adults. The aim of study was to find out whether a week-long oral treatment with L-lysine (2.64 g per day) and L-arginine (2.64 g per day) reduces trait and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 42 publications
1
32
0
Order By: Relevance
“…The albumin and globulin proteins in kidney bean proteins have shown high contents of lysine and arginine making this protein an important potential ingredient for food fortification. This is because dietary supplementation of foods with basic amino acids has been shown to normalize hormonal stress responses in human beings with high trait anxiety (Smriga, Ando, Akutsu, Furukawa, Miwa & Mo-rinaga, 2007). The results obtained for the globulin, including the amino acid composition, protein solubility, WHC, foaming capacity, foam stability, emulsion capacity, and emulsion stability compared favorably with those reported for most legume seeds.…”
Section: Resultsmentioning
confidence: 85%
“…The albumin and globulin proteins in kidney bean proteins have shown high contents of lysine and arginine making this protein an important potential ingredient for food fortification. This is because dietary supplementation of foods with basic amino acids has been shown to normalize hormonal stress responses in human beings with high trait anxiety (Smriga, Ando, Akutsu, Furukawa, Miwa & Mo-rinaga, 2007). The results obtained for the globulin, including the amino acid composition, protein solubility, WHC, foaming capacity, foam stability, emulsion capacity, and emulsion stability compared favorably with those reported for most legume seeds.…”
Section: Resultsmentioning
confidence: 85%
“…Lysine supplement has been shown to reduce trait anxiety and dampen the acute stress response in humans with lysine deficiency (Smriga, Ghosh, Mouneimne, Pellett, & Scrimshaw, 2004). In healthy males, state and trait anxiety as well as basal salivary cortisol were reduced after one week L-lysine and L-arginine supplementation (Smriga et al, 2007). L-lysine and L-arginine supplementation has also been found to increase neuroendocrine responses to acute psychosocial stress in subjects with high trait anxiety (Jezova, Makatsori, Smriga, Morinaga, & Duncko, 2005).…”
Section: Discussionmentioning
confidence: 98%
“…L-lysine and L-arginine supplementation has also been found to increase neuroendocrine responses to acute psychosocial stress in subjects with high trait anxiety (Jezova, Makatsori, Smriga, Morinaga, & Duncko, 2005). Smriga and colleagues hypothesized that lysine acts as a partial serotonin receptor 4 antagonist and simultaneously as a partial benzodiazepine agonist (Smriga et al, 2007). High lysine abundance in ED patients could indicate desensitization of receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have shown that intake of Llysine (Lys) and L-arginine (Arg) reduces state anxiety and lowered sympathetic nerve activity in healthy humans through the serotonin and benzodiazepine receptor (Smriga et al, 2007). Lys accounts for 7.4% and Arg accounts for 2.7% of the casein hydrolysate used in this experiment, and thus these compounds in the casein hydrolysate may play a role in controlling mood and physiological indicators.…”
Section: Discussionmentioning
confidence: 88%